2012
DOI: 10.1121/1.4756928
|View full text |Cite
|
Sign up to set email alerts
|

Brown meagre vocalization rate increases during repetitive boat noise exposures: A possible case of vocal compensation

Abstract: This study investigated whether or not boat noise causes variations in brown meagre (Sciaena umbra) vocalizations recorded in a nearshore Mediterranean marine reserve. Six nocturnal experimental sessions were carried out from June to September 2009. In each of them, a recreational boat passed over vocalizing fish 6 times with 1 boat passage every 10 min. For this purpose three different boats were used in random order: an 8.5-m cabin-cruiser (CC), a 5-m fiberglass boat (FB), and a 7-m inflatable boat (INF). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 36 publications
1
40
1
Order By: Relevance
“…In this context, the impact of anthropogenic noise on wildlife has drawn an increasing interest among bioacousticians in the past years, notably with studies on city noise pollution effects on birds [2227], road noise effects on frogs [28,29] and marine noise effects on fishes and marine mammals [3032]. Despite these studies, the effect of natural noise on the ecology and evolution of animal species is rarely investigated [33,34], and ambient noise level remains an underused variable in ecological studies [3539].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the impact of anthropogenic noise on wildlife has drawn an increasing interest among bioacousticians in the past years, notably with studies on city noise pollution effects on birds [2227], road noise effects on frogs [28,29] and marine noise effects on fishes and marine mammals [3032]. Despite these studies, the effect of natural noise on the ecology and evolution of animal species is rarely investigated [33,34], and ambient noise level remains an underused variable in ecological studies [3539].…”
Section: Introductionmentioning
confidence: 99%
“…This information, however, requires support from additional studies that include visual observations. A short‐term increase in calling activity was recorded when different boat types passed over vocalizing brown meagre in a nearshore Mediterranean marine reserve (Table ) (Picciulin et al., ). The fish's mean pulse rate increased after several boats passed in an experiment (Figure ).…”
Section: Effects Of Noise On Sound Communicationmentioning
confidence: 99%
“…Picciulin et al. () argued that this behavioural change may be a case of vocal compensation for impaired intraspecific communication.…”
Section: Effects Of Noise On Sound Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between noise and rattle rate was more robust. Some studies have found different repetition rates of acoustic elements (e.g., songs, elements, pulses) associated with different noise levels: in birds (e.g., Slabbekoorn and Smith 2002;Slabbekoorn and den Boer-Visser 2006), fishes (Picciulin et al 2012), whales (Lesage et al 1999), and frogs (Kaiser and Hammers 2009). It remains to be investigated whether different rattle rates convey a detection advantage in noisy conditions.…”
Section: Behav Ecol Sociobiolmentioning
confidence: 99%